2006
DOI: 10.1007/s10336-005-0011-y
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive responses of two related coexisting songbird species to environmental changes: global warming, competition, and population sizes

Abstract: Comparative analyses of interspecific differences in response to climate change can provide important insights into the factors initiating seasonal onset of reproduction in various species and subsequent fitness consequences. We present a comparative analysis based on a 30-year breeding survey of two related migratory songbird species [Reed Warbler Acrocephalus scirpaceus (RW) and Great Reed Warbler A. arundinaceus (GRW)], which coexist in reedbeds by means of various interspecific interactions. The RW advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 35 publications
2
44
0
Order By: Relevance
“…Crick (Schaefer et al 2006), the Polish population did not shift its end, causing an extension of the breeding season (Halupka et al 2008). A different pattern was reported by Weatherhead (2005) in a study on Red-winged Blackbirds Agelaius phoeniceus .…”
Section: Trends In Breeding and Climatementioning
confidence: 85%
See 1 more Smart Citation
“…Crick (Schaefer et al 2006), the Polish population did not shift its end, causing an extension of the breeding season (Halupka et al 2008). A different pattern was reported by Weatherhead (2005) in a study on Red-winged Blackbirds Agelaius phoeniceus .…”
Section: Trends In Breeding and Climatementioning
confidence: 85%
“…Given that there is a strong within-season decline in clutch size among bird species (Crick et al 1993), our data suggest that the Fieldfares' increase in mean brood size is caused by shifting its entire breeding season toward earlier dates, while in Song Thrushes the decline is driven by extending its breeding season with many late small-clutched broods. A long-term increase in brood size has been found in other open-nesting species, for example, Red-backed Shrikes Lanius collurio (Hušek & Adamík 2008), Eurasian Reed Warblers Acrocephalus scirpaceus and Great Reed Warblers Acrocephalus arundinaceus (Schaefer et al 2006, but see Halupka et al 2008).…”
Section: Trends In Breeding and Climatementioning
confidence: 92%
“…several Acrocephalus warblers: 25 (Schäfer et al, 2006;Rolando and Palestrini, 1991), and a triangle of interacting Sylvia warblers: S. borin/S. atricapilla/S.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a higher productivity of offspring related to climate-driven favourable conditions on the breeding grounds may counterbalance this effect. For example, studies of two populations of Reed Warblers from central Europe (Schaefer et al 2006;Halupka et al 2008) revealed that increased temperatures observed in recent years during the breeding season were correlated with a higher number of nestlings produced by breeding pairs. However, as various recent estimations of population trends for the Reed Warbler have produced equivocal results (Ockendon et al 2012(Ockendon et al , 2014Vickery et al 2014, Inger et al 2015, further detailed studies are needed.…”
Section: Discussionmentioning
confidence: 99%